Pengenalan Pencegahan Osteoporosis dan Pemeriksaan Keseimbangan pada Masyarakat - Suci Wahyu Ismiyasa; Mona Oktarina; Farahdina Bachtiar; Rena Mailani; Agustiyawan Agustiyawan; Ika Fitri Wulan Dhari; Fidyatul Nazhira; Rabia Rabia; Kiki Rezki Faradillah; Heri Wibisono; Andi Sirada; Eko Prabowo; Jessi Ferani; Zulia Akromatul Azizah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Osteoporosis is a bone disease that commonly occurs in the elderly. Prevention of osteoporosis includes proper nutrition, healthy lifestyle, and exercise to maintain body balance to prevent falls. In this community service program, we aimed to increase participants' knowledge of osteoporosis and prevention through education and balance testing. Our method involved taking vital signs and balance tests with the Fukuda stepping test, followed by a presentation on osteoporosis. Participants were asked to fill out a five-item multiple-choice questionnaire before and after the presentation. The results showed that all participants demonstrated enthusiasm and significant knowledge improvement after the education and balance testing, with the test scores increasing from 93.18% to 100%. This finding indicates that providing education and balance testing can increase participants' knowledge about osteoporosis prevention and help reduce the risk of falls in osteoporosis patients.